IMPLEMENTASI METODE AGGLOMORATIVE HIERARCHICAL CLUSTERING PADA WEBSITE PEMILIHAN TEMPAT FUTSAL STUDI KASUS KOTA DEPOK - Aditya Pratama; Desi Arisandi; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
This application was made for the selection of futsal fields in the city of Depok. This application was made using the Agglomorative Hierarchical Clustering method which aims to recommend criteria for rental rates, distances, canteen facilities, toilet facilities and changing room facilities. This application will provide the recommended criteria based on the distance between the customer and the futsal location. Futsal place data is taken from futsal places in Depok City. The results of the Agglomorative Hierarchical Clustering method are the criteria values placed on the futsal field information.